Integrating open educational resources in general english courses to strengthen speaking skill - Angélica María Moya Pachón (Corporación Universitaria Minuto de Dios, 2015)
The current research integrated Open educational resources -OER- in a general english course at Uniminuto, a private university located in Bogotá. The primary objective was to innovate the process of teaching English as a foreign language through the use of Open educational resources to develop speaking skills in students with a B1.1 level. As a result, it was possible to identify that the OER allowed students to improve the way they speak and communicate with others in English. Moreover, the resources helped the students to develop an autonomous learning style and improve their digital skills.